STRATEGIC CONTROL OF THE ARCTIC AND POSSIBLE ARMED CONFLICT OF THE GREAT POWERS - Tomić, Miloš (The Policy of National Security, 2023)
The geopolitical competition of great powers over the control of strategically important natural resources is an integral part of the political agenda aimed at achieving economic and thus military dominance on a global level. The territory of the Arctic, as the northernmost part of the planet Earth, has large reserves of natural resources (primarily oil and gas), the sovereign control and exploitation of which are contested by the countries that surround (a total of eight of them) this area, but also recently by countries that have granted themselves the status of "near arctic state" such as the People's Republic of China. The trend of accelerated militarization of the Arctic in the period after the end of the Cold War can be interpreted as a consequence of the damaged relationship between the key actors of international politics and different perceptions of the future global order. The goal of this work is a systematic description of the dynamics of relations between Arctic states with a special focus on the USA (including NATO) and the Russian Federation and their activities in the military-defense sphere. In order to achieve the projected goal, the technique of content analysis of strategic documents, the technique of narrative analysis and historical comparative analysis was used. The results of this research indicate the increased interest of the great powers in controlling the Arctic, i.e. the natural resources present in this area, as well as the strategically important international traffic corridor, the Northern Sea Route. Accordingly, the engagement of the armed forces should enable the unhindered implementation of the defined political-economic activities of the Arctic states with the status of a great power.
Keywords: Arctic; natural resources; militarization; control; Northern Sea Route